2022
DOI: 10.1002/mp.15972
|View full text |Cite
|
Sign up to set email alerts
|

LiSNet: An artificial intelligence ‐based tool for liver imaging staging of hepatocellular carcinoma aggressiveness

Abstract: Background Presurgical assessment of hepatocellular carcinoma (HCC) aggressiveness can benefit patients’ treatment options and prognosis. Purpose To develop an artificial intelligence (AI) tool, namely, LiSNet, in the task of scoring and interpreting HCC aggressiveness with computed tomography (CT) imaging. Methods A total of 358 patients with HCC undergoing curative liver resection were retrospectively included. Three subspecialists were recruited to pixel‐wise annotate and grade tumor aggressiveness based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition to detecting relationships within large multi-omic data sets to improve prognostication, AI techniques can help us identify biomarkers in the preoperative setting typically only identified through pathologic evaluation such as microvascular invasion (MVI) [28]. For example, multiple studies have shown the feasibility of using machine learning algorithms to accurately predict the presence of MVI based on preoperative axial imaging characteristics [29][30][31]. Chong et al built a radiomic-based nomogram to assess the risk of MVI [32].…”
Section: Hcc Prognosis and Risk Of Recurrencementioning
confidence: 99%
“…In addition to detecting relationships within large multi-omic data sets to improve prognostication, AI techniques can help us identify biomarkers in the preoperative setting typically only identified through pathologic evaluation such as microvascular invasion (MVI) [28]. For example, multiple studies have shown the feasibility of using machine learning algorithms to accurately predict the presence of MVI based on preoperative axial imaging characteristics [29][30][31]. Chong et al built a radiomic-based nomogram to assess the risk of MVI [32].…”
Section: Hcc Prognosis and Risk Of Recurrencementioning
confidence: 99%
“…As a powerful tool, deep learning can provide objective references for doctors and further improve their work efficiency [ 18 , 19 ]. Therefore, it is widely used in thyroid cancer [ 20 ], cervical cancer [ 21 ], liver cancer [ 22 , 23 ], and other diseases to improve the diagnostic efficiency [ 24 ]. And in endometrial diagnosis, deep learning is usually used for segmentation and classification tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, advancements in artificial intelligence (AI) capabilities have shown great potential to redefine the way we navigate clinical care for HCC patients. AI has the capacity to improve risk prediction in chronic hepatitis patients [13], accelerate the diagnostic process with early identification of HCC [14][15][16] , increase accuracy in the classification of liver lesions and HCC subtypes [17][18][19][20] , tumor staging [21] , and survival prediction [22,23] . Decisions regarding candidate selection and optimal treatment methods may also utilize AI in the prediction of treatment response, progression-free and overall survival [24,25] and risk of HCC recurrence [26] .…”
Section: Introductionmentioning
confidence: 99%